2016
DOI: 10.3758/s13414-015-1027-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sustained inattentional blindness and working memory capacity

Abstract: Inattentional blindness, whereby observers fail to detect unexpected stimuli, has been robustly demonstrated in a range of situations. Originally research focused primarily on how stimulus characteristics and task demands affect inattentional blindness, but increasingly studies are exploring the influence of observer characteristics on the detection of unexpected stimuli. It has been proposed that individual differences in working memory capacity predict inattentional blindness, on the assumption that higher w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…As hypothesized, the working memory score did not predict the propensity to remain aware of the auditory alarms. This result is in line with previous studies that report an absence of relation between the working memory span and the occurrence of inattentional blindness (Beanland & Chan, 2016;Bredemeier & Simons, 2012;Kreitz et al, 2016a;Kreitzet al, 2016b) or inattentional deafness (Kreitzet al, 2016b). Though working memory capacity-as a measure of cognitive resources at a centrallevel-has been shown to be related to individuals' sustained and divided attentional performance (Colflesh & Conway, 2007;Sörqvist et al, 2012;Unsworth & Engle, 2007), this construct seems not appropriated to account for inattentional deafness.…”
Section: Discussionsupporting
confidence: 93%
“…As hypothesized, the working memory score did not predict the propensity to remain aware of the auditory alarms. This result is in line with previous studies that report an absence of relation between the working memory span and the occurrence of inattentional blindness (Beanland & Chan, 2016;Bredemeier & Simons, 2012;Kreitz et al, 2016a;Kreitzet al, 2016b) or inattentional deafness (Kreitzet al, 2016b). Though working memory capacity-as a measure of cognitive resources at a centrallevel-has been shown to be related to individuals' sustained and divided attentional performance (Colflesh & Conway, 2007;Sörqvist et al, 2012;Unsworth & Engle, 2007), this construct seems not appropriated to account for inattentional deafness.…”
Section: Discussionsupporting
confidence: 93%
“…However, we think this is unlikely. There have been several attempts in the literature at linking individual differences in cognitive capacities and IB (e.g., Beanland & Chan, 2016; Bredemeier & Simons, 2012; Kreitz, Furley, Memmert, & Simons, 2015), and these studies have systematically failed to find such a relationship. The same is true regarding differences in emotional profiles among individuals: Differences in factors like negative affect, anhedonic depression, anxious arousal, and worry alone do not predict differences in IB either (Bredemeier, Hur, Berenbaum, Heller, & Simons, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that individuals with greater information processing capacity (i.e., higher working memory span) exhibit superior ability with respect to divided and sustained attention (Colflesh and Conway, 2007;Unsworth and Engle, 2007), and therefore, should be less susceptible to the effects of inattention during the performance of demanding tasks. However, this hypothesis is contradicted by the absence of any correlation between individual differences in processing capacity and the occurrence of inattentional blindness (Bredemeier and Simons, 2012;Beanland and Chan, 2016;Kreitz et al, 2016a) or deafness (Kreitz et al, 2016b;Dehais et al, 2019).…”
Section: Toward a Limit Of The Theory Of Limited Resourcesmentioning
confidence: 99%